Manajemen Masjid dalam Pengembangan Dakwah di Masjid Agung Baitussalam Purwokerto - Aqlia Ismi Asqiah; Ahmad Asrof Fitri; Sobirin Sobirin (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
This study aims to analyze the implementation of management functions, the development of Islamic propagation (dakwah), as well as the supporting and inhibiting factors in the management of the Baitussalam Grand Mosque in Purwokerto. The research employs a qualitative approach with structured interviews conducted with mosque administrators, community leaders, and congregants. Data were collected through observation, interviews, and documentation. The findings indicate that the Baitussalam Grand Mosque applies management functions such as planning, organizing, staffing, directing, and controlling. The developed dakwah activities include regular study sessions, religious gatherings for elderly women, Qur'anic Education Parks (TPQ), and special activities during Ramadan. Supporting factors for successful mosque management include regular funding from congregants through donation boxes and benefactors, spacious building infrastructure, adequate facilities, and solid teamwork among administrators. However, challenges include limited government funding, a lack of sufficient mosque courtyard space, and less supportive surrounding environmental conditions.This study highlights the importance of enhancing mosque empowerment to maximize its social benefits within the community.